NSCLC patients with rare EGFR Ex19del/G724S mutation showed good response to afatinib combined with chemotherapy treatment: A two-case report - Wang, Huilin; Yu, Qitao; Shi, Lina; Hou, Qinhan; Dan, Liang; Liang, Chuqiao; Hong, Xiaoyu; Zhao, Yun; Ning, Ruiling (Frontiers in Oncology, 2022)
EGFR G724S mutation in exon 18 has been shown to be resisted to both first- and third-generation EGFR-TKIs. However, we found a rare mutation of EGFR Ex19del/G724S in two patients with lung cancer who achieved a favorable response to the combination of afatinib and chemotherapy. Identified by next-generation sequencing (NGS), the EGFR G724S was found from a primary and a secondary tumor biopsy respectively. Treated with afatinib combined with chemotherapy, both patients had responded well and achieved progressive-free survival. Analysis of acquired mutations at afatinib progression revealed that the emergence of EGFR T790M or ALK fusion was the potential mechanism of afatinib resistance. Our study lends credence to the treatment of afatinib combined with chemotherapy as a viable option for patients with Ex19del/G724S.